The metabolic cost of physical activity in mice using a physiology-based model of energy expenditure - Vojtěch Škop; Juen Guo; Naili Liu; Cuiying Xiao; Kevin D. Hall; Oksana Gavrilova; Marc L. Reitman (Elsevier, 2023)
Objective: Physical activity is a major component of total energy expenditure (TEE) that exhibits extreme variability in mice. Our objective was to construct a general, physiology-based model of TEE to accurately quantify the energy cost of physical activity. Methods: Spontaneous home cage physical activity, body temperature, TEE, and energy intake were measured with frequent sampling. The energy cost of activity was modeled considering six contributors to TEE (basal metabolic rate, thermic effect of food, body temperature, cold induced thermogenesis, physical activity, and body weight). An ambient temperature of 35 °C was required to remove the contribution from cold induced thermogenesis. Basal metabolic rate was adjusted for body temperature using a Q10 temperature coefficient. Results: We developed a TEE model that robustly explains 70-80% of the variance in TEE at 35 °C while fitting only two parameters, the basal metabolic rate and the mass-specific energy cost per unit of physical activity, which averaged 60 cal/km/g body weight. In Ucp1−/− mice the activity cost was elevated by 60%, indicating inefficiency and increased muscle thermogenesis. The diurnal rhythm in TEE was quantitatively explained by the combined diurnal differences in physical activity, body temperature, and energy intake. Incorporating body temperature into human basal metabolic rate measurements significantly reduced the inter-individual variation. Conclusions: The physiology-based model of TEE allows quantifying the energy cost of physical activity. While applied here to mice, the model should be generally valid across species. Due to the effect of body temperature, we suggest that basal metabolic rate measurements be corrected to a reference body temperature, including in humans. Having an accurate cost of physical activity allows mechanistic dissection of disorders of energy homeostasis, including obesity.